KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Rita Hayati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine the leadership characteristics of principals in improving teacher performance. This research was conducted using inductive qualitative methods. Data collection is done by interview, observation, documentation study, and study of research results. The results of this study indicate that the leadership characteristics of principals who can improve teacher performance include 1) educational staff capacity building programs through training, workshops, seminars and Subject Matter Teacher Discussion (SMTD); 2) the ability of the principal to carry out the process of control, guidance and supervision; 3) giving motivation; 4) good communication; and 5) democratic leadership style.